2000
DOI: 10.1051/rnd:2000100
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and NF-$\kappa$B by quercetin in growing murine L1210 lymphocytic leukaemic cells potentiated by TNF-$\alpha$

Abstract: -Polyphenol quercetin induced apoptosis in proliferating murine L1210 lymphocytic cells. DNA damage, as well as apoptosis and withdrawal from the cell cycle were transient. The above mentioned death promoting activity of quercetin was enhanced by physiological concentrations of TNF-α. At the same time, indices of cell viability dropped. However, the extent and tendency of the initially enhanced cell mortality steadily diminished throughout the experiment. After 12 h the G2/M phase reappeared. After 24 h all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 91 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…This assumption is reinforced by our experiments in which we observed minimal toxicity in primary human fibroblasts and mesenchymal stromal/stem cells upon incubation with quercetin and sulforaphane (11). Our data are consistent with the findings of Orzechowski et al (27) who demonstrated quercetin-induced enhanced binding of p65/cRel containing NF-κB dimers in nuclear extracts of murine lymphocytic leukemia cells. Conversely, other authors show inhibition of NF-κB binding activity in response to quercetin (19,28).…”
Section: Discussionsupporting
confidence: 93%
“…This assumption is reinforced by our experiments in which we observed minimal toxicity in primary human fibroblasts and mesenchymal stromal/stem cells upon incubation with quercetin and sulforaphane (11). Our data are consistent with the findings of Orzechowski et al (27) who demonstrated quercetin-induced enhanced binding of p65/cRel containing NF-κB dimers in nuclear extracts of murine lymphocytic leukemia cells. Conversely, other authors show inhibition of NF-κB binding activity in response to quercetin (19,28).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, quercetin-mediated apoptosis may be related to many factors such as stress proteins, disruption of microtubules, nuclear factor B, Cox-2, p53, survivin, c-Jun NH 2 -terminal kinase, mitogenactivated protein kinase kinase-extracellular signal-regulated kinase, Bcl-2 family proteins, heat shock proteins, DNA topoisomerase II, release of cytochrome c, and activation of caspases (Yoshida et al, 1990;Orzechowski et al, 2000;Choi et al, 2001;Jakubowicz-Gil et al, 2002;Kaneuchi et al, 2003;Cheong et al, 2004;Kuo et al, 2004;Nguyen et al, 2004;Ong et al, 2004). Quercetin has been reported to inhibit the growth of various human cancers, including leukemia, breast, esophagus, colon, prostate, nasopharyngeal, endometrial, and lung cancers (Yoshida et al, 1990;Orzechowski et al, 2000;Choi et al, 2001;Jakubowicz-Gil et al, 2002;Kaneuchi et al, 2003;Cheong et al, 2004;Kuo et al, 2004;Nguyen et al, 2004;Ong et al, 2004). It is imperative to investigate the biological effects of quercetin glucuronides that are more close to the in vivo situation.…”
mentioning
confidence: 99%
“…Sato et al [87] or Ishikawa et al [43] reported the suppression of NF-kB activation by quercetin in human synovial cells, or glomerular cells, respectively, but the cells were studied in serum free medium, with additional one day fasting as the pretreatment period to induce cell quiescence. We reported transient activation of this transcription factor by quercetin in conditions favoring cell proliferation [77]. It therefore appears, that quercetin-induced NF-kB activation is characterized by cell specificity.…”
Section: Modulation Of Signal Transduction Cascadesmentioning
confidence: 71%
“…On the contrary, flavonoids are cytopathic to tumor cells. The puzzling issue of the developing resistance of tumor cells to cytopathic actions of flavonols in the presence of TNF-a-stimulated NF-kB activity remains unexplained and ambiguous [77].…”
Section: Modulation Of Signal Transduction Cascadesmentioning
confidence: 99%